Pengaruh Pemahaman Peraturan Perpajakan, Kesadaran Wajib Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak UMKM (Studi Kasus Wajib Pajak di KPP Pratama Tangerang Timur) - Suhadi, Aprilia (Politeknik Raflesia Press, 2025)
The compliance of MSME taxpayers is influenced by their understanding of tax regulations, their awareness as taxpayers, and the enforcement of tax sanctions as stipulated by law. This study aims to analyze the influence of understanding tax regulations, taxpayer awareness, and tax sanctions on the compliance of MSME taxpayers at the East Tangerang Pratama Tax Service Office. A quantitative research method was applied using attribution theory as the analytical framework. The population consisted of 1,760 MSME taxpayers, with 95 respondents selected through a random sampling technique. Data were collected using a structured questionnaire and analyzed with multiple linear regression using SPSS version 26. The results show that partially, understanding of tax regulations, taxpayer awareness, and tax sanctions each have a positive and significant effect on MSME taxpayer compliance. Simultaneously, these three factors significantly influence taxpayer compliance, indicating that improving knowledge, awareness, and consistent enforcement of sanctions can enhance compliance levels among MSME taxpayers at the East Tangerang Pratama Tax Service Office.